RANCANG BANGUN SIMULATOR PENGENDALIAN LIFT 6 LANTAI BERBASIS PLC - Abdurrohman Sudaesi; Giri Wahyu Wiriasto; Paniran Paniran (JTIKA (Jurnal Teknik Informatika, Komputer dan Aplikasinya), 2022)
Elevator is a vertical means of transportation that requires a control system to change floor positions. The controller used in this research is a Programable Logic Controller (PLC). In PLCs, the designed logic is represented in ladder diagrams and embedded in internal memory. The design of the elevator simulator uses a board measuring 30cmx40cm, consisting of a PLC unit, several electronic components such as LEDs, on-off switches, cables, resistors, external power supply for the LED circuit power source as an output indicator. In the test, the LED will actively adjust to the logic design in the ladder diagram. The illustration of the control of a 6-floor elevator is described in the LED circuit simulator, including as an indicator of the movement of the elevator to each floor and a switch as a representation of the limit switch sensor and the pointer button for other purposes in a work process on the 6-floor elevator system. The logic of the system is built from 30 input indicators and 22 output indicators. After several stages of the test scenario have been carried out, the control logic that has been designed can work well.